Manual para el desarrollo de las inteligencias múltiples en niños y niñas de 4 a 5 años del CIB María Auxiliadora del barrio Santa Clara. - Sánchez, Tráncito (2013)
The theory of Multiple Intelligences developed by Howard Gardner, breaks the traditional concept of intelligence suggests that intelligence is a capacity, not only but multifactorial, which is aimed at solving problems. From a traditional view and from the practical learning experience, not all human abilities (multiple intelligences) have been recognized as important in human development. It was considered that only certain skills are important for learning and according to them, has declared human beings as intelligent or not. The present study aims to reassess the various human capacities of children through play and recreational activities that enable them to strengthen their multiple intelligences.